2002
DOI: 10.1002/rcm.744
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nebulizing and drying gas flow on capillary electrophoresis/mass spectrometry

Abstract: This study was focused on examining the influence of gas flow parameters on capillary electrophoresis/mass spectrometry (CE /MS) performance using sheath-liquid CE /MS interfaces. The effects of nebulizing and drying gas velocity and drying gas temperature on CE separation and MS detection sensitivity were systematically determined. Nebulizing gas velocity was observed to be a critical parameter in the optimization of CE /MS method, since it affected both MS detection sensitivity, and also CE separation effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 17 publications
7
67
1
1
Order By: Relevance
“…Increasing the content of volatile solvent also has this effect. The sheath gas may increase the speed of the solution in the capillary by suction effect [119] and thus reduce analysis time. We showed that this effect is dependent on the speed of the buffer (pH-dependency).…”
Section: Sheath Gas Conditionsmentioning
confidence: 99%
“…Increasing the content of volatile solvent also has this effect. The sheath gas may increase the speed of the solution in the capillary by suction effect [119] and thus reduce analysis time. We showed that this effect is dependent on the speed of the buffer (pH-dependency).…”
Section: Sheath Gas Conditionsmentioning
confidence: 99%
“…Using this approach RSD% values down to 7.8% (n = 101) for the analyte used to optimize the system without application of an internal standard could be achieved [4]. The nebulizer gas pressure has a strong influence on detection time because of the suction effect [35]. Thus, low values should be applied in order to achieve stable conditions, e.g., by preventing of air entrance into the capillary during the injection process and to avoid the loss of separation.…”
Section: Quantitative Aspects Of Ce-esi-ms Couplingmentioning
confidence: 99%
“…ESI is the method of choice for producing gas phase ions from solution because it is a very soft ionization method and is useful for the ionization of larger molecules or biomolecules. ESI-MS can be used for the analysis of complex mixtures [1][2][3][4][5] and is commonly used to couple separation techniques, such as high performance liquid chromatography (HPLC) [6][7][8][9], capillary electrophoresis (CE) [10][11][12][13][14][15][16][17][18][19][20][21], or microchannel electrophoresis (ME) [22][23][24][25][26][27][28][29] with MS. Many sample introduction methods, particularly those that employ separations, rely on pressure driven flow for sample introduction.…”
Section: Introductionmentioning
confidence: 99%
“…For optimal sample utilization, determination of the parameters that provide the highest signal intensity is crucial. Many previous studies have been performed to optimize different parameters that affect the ESI signal, like sheath flow [10,12,20], nebulizing gas [13,16], buffer systems [20,30], and ESI voltage [31,32]. Likewise, ESI emitters have been extensively studied because the characteristics of the emitter, such as the emitter i.d., the surface area of the emitter orifice, and the hydrophobicity, have a great impact on the observed ESI signal; in addition to influencing the working parameters of the system, such as flow rate or ESI voltage [33].…”
Section: Introductionmentioning
confidence: 99%